2004
DOI: 10.1097/01.ccm.0000127263.54807.79
|View full text |Cite
|
Sign up to set email alerts
|

Daily interruption of sedative infusions and complications of critical illness in mechanically ventilated patients*

Abstract: Daily interruption of sedative infusions in critically ill patients undergoing mechanical ventilation reduces intensive care unit length of stay and, in turn, decreases the incidence of complications of critical illness associated with prolonged intubation and mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
169
1
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(183 citation statements)
references
References 31 publications
1
169
1
12
Order By: Relevance
“…Studies by Brook et al and Kress et al have demonstrated that protocols for sedative and analgesic administration with the goal of minimizing constant infusions led to reduced DOMV (22,113). Furthermore, daily interruption of sedation results in a reduced incidence of intensive care unit complications, in which VAP was included (127,180). Weaning protocols have also resulted in reduced DOMV, whether respiratory therapist initiated or not (59,67).…”
Section: Preventionmentioning
confidence: 99%
“…Studies by Brook et al and Kress et al have demonstrated that protocols for sedative and analgesic administration with the goal of minimizing constant infusions led to reduced DOMV (22,113). Furthermore, daily interruption of sedation results in a reduced incidence of intensive care unit complications, in which VAP was included (127,180). Weaning protocols have also resulted in reduced DOMV, whether respiratory therapist initiated or not (59,67).…”
Section: Preventionmentioning
confidence: 99%
“…[28] Use of lighter sedation may reduce the rate of ICU-acquired neuromuscular weakness. [29][30] In this study, patients in the two groups were given daily interruption of sedation or no sedatives.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] When compared to the current literature, we observed that the EPs in Turkey are using sedative and paralyzing drugs less frequently. This result suggests that there may be a deficiency in the knowledge and experience in MVM in Turkey.…”
Section: Discussionmentioning
confidence: 78%